StudySync Mobile Application Design for Student Academic Activity Management Based on SQLite Database - Arsyanda; M. Miftach Fakhri; Pramudya Asoka Syukur; Devi Miftahul Jannah; Elma Nur Jannah; Annajmi Rauf (Program Studi Teknik Komputer, 2024)
The development of information and communication technology has made significant contributions in various sectors, including education. Mobile applications have become an effective solution in improving time management and reducing academic procrastination among students. This research aims to design and develop a mobile application called StudySync that utilizes SQLite database to assist students in organizing their academic activities. The development method used is the Agile method with three sprint cycles, ensuring incremental improvements and continuous validation of features. The application offers task management features, note-taking, reminders, and a search system to facilitate the management of academic information. SQLite was chosen as the main database due to its self-contained, serverless, zero-configuration, and transactional nature, suitable for mobile applications that require fast and reliable database access. The test results show that the StudySync application successfully meets the needs of users in organizing academic assignments and notes and improving student time management.